Characterization of Neurospora crassa albino mutants that were previously unassigned to locus - M. Schumacher; Yi-Zhong Liu; Hongjian Liu; T. J. Schmidhauser (Fungal Genetics Reports, 1995)
Neurospora crassa mutant hunts by various groups have identified albino (al) mutants that map to the al-1 - al-2 region on the right arm of linkage group I. The cloning of the al-1 and al-2 genes (Schmidhauser et al. 1990 Mol. Cell. Biol. 10:5064-5070, Schmidhauser et al. 1994 J. Biol. Chem. 269:12060-12066) allows assignment of locus to the above mutants by DNA mediated transformation. Analysis of phytoene desaturases from different organisms indicates at least three types of enzymes as defined by the number of desaturation steps carried out (Sandmann 1994 J. Plant Physiol. 143:444-447). The N. crassa phytoene desaturase, the al-1 gene product, introduces four double bonds converting phytoene to lycopene. Of the three intermediates in this reaction sequence two are colored. The occurrence of visibly distinguishable albino alleles in N. crassa has been noted (Perkins 1989 Fungal Genetics Newsl. 36:63). Assignment of locus to N. crassaalbino alleles represents a first step in the functional characterization of N. crassa carotenogenic loci.